Analysis of Sanitation Infrastructure on the Incidence of Dermatitis in the Sungsang Slum Area, Banyuasin II District, Banyuasin Regency - Yulinda, Yulinda; Sunarsih, E.; Utami, Venie Putriyana; Ramadhanti, R. (PT. Hafasy Dwi Nawasena, 2024)
This study aims to analyse the relationship between sanitation infrastructure and the incidence of dermatitis. The location was in Sungsang Slum Area, Banyuasin II District, Banyuasin Regency, South Sumatra Province. This study is an analytical observational study using cross sectional study design including univariate and bivariate analysis, using chi-square test (α < 0.05). The results showed a significant relationship between access to water, fulfilment of water needs, drainage conditions, household waste disposal and waste transportation from home to temporary/final disposal site with the incidence of dermatitis, while no significant relationship was found between access and technical feasibility of defecation facilities with the incidence of dermatitis. This study emphasises the importance of improving sanitation infrastructure in slums to reduce health risks such as dermatitis. Further research and co-operation between the government, NGOs and communities is needed to effectively address the slum challange and improve the health and well-being of the community.